Sowing Innovation: Entrepreneurial Opportunities in Perennial Crop and Nursery Management for Rural Development - Chiquito Chilan, Roxana; Castillo Palacios, Carlos; Muñoz Valle, Marcia; Quiñonez Martinez, Cecilia (LACCEI, 2025)
This article examines how education in perennial crops and nurseries, supported by innovative pedagogical management, can open entrepreneurial opportunities for students, contributing to sustainable rural development. It analyzes sustainable practices, the use of modern technologies, such as precision agriculture, and environmental management, which can be foundations for students to design and manage agricultural ventures, such as commercial nurseries or high-value perennial crops, highlighting the social and economic impact of these ventures on local communities. The article emphasizes the importance of integrating sustainable practices and innovative technologies into agricultural education. This not only improves learning but also prepares students to identify and take advantage of market opportunities by understanding sustainability and economic management, which are essential for developing entrepreneurs capable of innovating in the agricultural sector, particularly in rural areas of Ecuador. It links the educational approach to entrepreneurship, highlighting its potential to generate economic, social, and environmental impact on rural development, in line with the Sustainable Development Goals (SDGs)